EVENT-DRIVEN PROCESS ORCHESTRATION IN E-GOVERNANCE: MODELING ASYNCHRONOUS INTEGRATION PATTERNS - Saidov, Olim (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This paper presents a comprehensive analysis of event-driven process orchestration patterns in the E-Jarima digital governance platform, focusing on asynchronous integration modeling using Business Process Model and Notation (BPMN). The study examines the video processing pipeline and administrative review workflows to demonstrate how modern e-governance systems can effectively handle complex, distributed processes through event-driven architectures. We propose a formal verification approach for analyzing message flows, asynchronous handoffs, and error compensation mechanisms in government digital transformation initiatives. Our analysis reveals that the combination of BPMN modeling with Communicating Sequential Processes (CSP) implementation provides a robust framework for ensuring deadlock-freedom and process reliability. The findings indicate that event-driven orchestration patterns significantly improve system scalability, with the E-Jarima platform successfully processing over 100,000 citizen reports annually through geographic distribution and parallel processing. This research contributes to the understanding of how formal business process modeling can guide the implementation of resilient, citizen-centric digital government services.